Comprender: propuesta de pivotes - Santiago Alonso (Pontificia Universidad Católica del Perú, 2011)
How do we understand? A pivot proposal The basic question is what it is needed to understand. The proposal is that understanding requires pivots, a useful word to integrate findings in different areas. In that sense, a pivot can be understood as a mental model. It can also be the body, an idea based on embodied cognition. But more fundamentally, our biology and brain are the central pivots for understanding. Therefore, this essay can be seen as a brief travel through three different subjects: Mental Models, Embodied Cognition and Cognitive Neuroscience, all of which are necessary to understand how a person understands.